Mosque Transparency under Frame Qur'an Surah At Taubah Verse 18: Analysis at the Mosque of Jogokariyan - Dessy Ekaviana; Iwan Triyuwono; Ali Djamhuri (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The purpose of this study is to formulate accountability policies at the Jogokariyan Mosque. The research was conducted using the Islamic ethnomethodology scheme. Via interviews with several Jogokariyan mosque takmirs, the information was collected. Direct observation is also performed so that the requisite data can be thoroughly obtained. The results of the exploration show four ways in which the takmir of the Jogokariyan Mosque performs accountability practices: 1) ensuring the best for the mosque's needs; 2) providing special needs facilities for pilgrims; 3) accommodating the fulfillment of congregational worship in Maliyah; and 4) providing social security for the community. In the four phases, mutual value is included. As mentioned in verse 18 of QS At-Taubah, the adoption of accountability practices in these four ways is based on the spirit of the prosperity of the mosque. In order to receive the happiness of Allah, the takmir of the Jogokariyan Mosque uses the entire course of transparency training